TECHNICAL EFICIENCY OF FISH AGGREGATING DEVICES ASSOCIATED WITH TUNA FISHERY IN KENDARI FISHING PORT – INDONESIA - Mohamad Natsir; Agustinus Anung Widodo; Wudianto Wudianto; Sveinn Agnarsson (Research Center for Fisheries, 2017)
Kendari fishing port is one of the biggest tuna fisheries landing in Indonesia. It yearly average tuna production was more than 20 thousand tons. The tuna fishing fleet in Kendari use FAD (Fish Aggregating Devices) as an auxiliary fishing gear. FAD management is major issues in Indonesian tuna fisheries. extensive investment on FAD has led to increase of the juvenile and by catch and also social problem because of the competition. Technical efficiency analysis was done during this study, 2015 catch and logistic data from Kendari fishing port was run using stochastic frontier to obtain the model. Mean value technical efficiency was 0.534. Purse seine the highest mean value compared to other fishing gear. All the variables input show positive relationship to the catch except the days at sea variables, this is a signal that the increasing number of FAD has made the fisherman spend more time at sea it will decrease the technical efficiency. The results support the need of FAD regulation done by the government of Indonesia. Regulation will keep the number of FAD at optimum level and increase the technical effieciency so the fisheries keep gaining the optimum benefit from the resources.